Exploring the relationship of potential new rhizobacteria metabolism with Lotus spp. performance in a rice-pasture rotation system - Maguire, Vanina Giselle; Rodríguez, Andrés Alberto; Alonso, Andrés Mariano; Ezquiaga, Juan Pedro; Salas, Nehuén; Llames, María Eugenia; Gortari, Maximiliano; Ayub, Nicolás Daniel; Brambilla, Silvina Maricel; Bouilly, Pedro José; Romero, Fernando Matías; Gárriz, Andrés; et al. (Springer, 2025)
The first objective of this study was to identify and characterize new strains isolated from rice–pasture rotation soils, capable of: (A) establishing efficient symbiosis with Lotus plants and (B) enhancing their performance under N-deficient soil conditions, outperforming the Lotus reference strain 700743. To test this, we used the trap plant technique to iso late native rhizobial strains from these soils. We characterized their potential through nodulation and plant performance parameters, including number of nodules, total nodule weight per plant, total leaf area, and stem parameters such as fresh weight, dry weight, and nitrogen content. These parameters were determined in plants inoculated with these strains in a nitrogen-restricted medium. As a second objective, we aimed to genetically characterize the strains previously selected and compare them with the reference strain. Two isolated strains were characterized, RIZ17 and RIZ20, both belonging to the genus Mesorhizobium, which showed plant performance similar to or greater than the reference strain 700743. In particular, RIZ17 outperformed the reference strain in nodulation and plant performance parameters of Lotus plants grown under nitrogen-deficient conditions. Genomic analysis did not reveal differences among the three strains at the gene sequence level related to nodulation and nitrogen fixation. However, it indicated differences in gene sequences linked to bacterial nutritional metabolism. These differences could provide an adaptive advantage to RIZ17 by efficiently metaboliz ing plant-derived nutrients, resulting in greater energy generation for symbiosis establishment and increased root nodule number and weight. The studied strains could be promising new rhizobia for inoculant formulation.